Can Emergency Physician Gestalt "Rule In" or "Rule Out" Acute Coronary Syndrome: Validation in a Multicenter Prospective Diagnostic Cohort Study. (23rd September 2019) - Oliver, Govind; Reynard, Charlie; Morris, Niall; Body, Richard
Abstract: Background: Chest pain is a common problem presenting to the emergency department (ED). Many decision aids and accelerated diagnostic protocols have been developed to help clinicians differentiate those needing admission from those who can be safely discharged. Some early evidence has suggested that clinician judgment or gestalt alone could be sufficient. Objectives: Our aim was to externally validate whether emergency physician's gestalt could "rule in" or "rule out" acute coronary syndromes (ACS). Methods: We performed a multicenter prospective diagnostic accuracy study including consenting patients presenting to the ED in whom the physician suspected ACS. At the time of arrival, clinicians recorded their perceived probability of ACS using a 5‐point Likert scale. The primary outcome was a diagnosis of ACS, defined as acute myocardial infarction or major adverse cardiac events within 30 days. Results: A total of 1, 391 patients were included; 240 (17.3%) had ACS. Overall, gestalt had fair diagnostic accuracy with a C‐statistic of 0.75 (95% confidence interval = 0.72 to 0.79). If ACS was "ruled out" in the 60 (4.3%) patients where clinicians perceived that the diagnosis was "definitely not" ACS, a sensitivity of 98.0% and negative predictive value of 95.0% could have been achieved. If ACS was only ruled out in patients who also had no electrocardiographic (ECG) ischemia and a normal initial cardiac troponin (cTn) concentration, 100.0% sensitivity and NPV could be achieved. However, this strategy only applied to 4.1% of patients. If patients with "probably not" ACS who had normal ECG and cTn were also ruled out ( n = 418, 30.8%), sensitivity fell to 86.2% with 99.2% NPV. Using gestalt "definitely" ACS to rule in ACS gave a specificity of 98.5% and positive predictive value of 71.2%. Conclusion: Clinician gestalt is not sufficiently accurate or safe to either rule in or rule out ACS as a decision‐making strategy. This study will enable emergency physicians to understand the limitations of our clinical judgment.